2023
DOI: 10.1038/s41698-023-00449-x
|View full text |Cite
|
Sign up to set email alerts
|

ALK fusions in the pan-cancer setting: another tumor-agnostic target?

Aditya Shreenivas,
Filip Janku,
Mohamed A. Gouda
et al.

Abstract: Anaplastic lymphoma kinase (ALK) alterations (activating mutations, amplifications, and fusions/rearrangements) occur in ~3.3% of cancers. ALK fusions/rearrangements are discerned in >50% of inflammatory myofibroblastic tumors (IMTs) and anaplastic large cell lymphomas (ALCLs), but only in ~0.2% of other cancers outside of non-small cell lung cancer (NSCLC), a rate that may be below the viability threshold of even large-scale treatment trials. Five ALK inhibitors –alectinib, brigatinib, ceritinb, crizotinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 185 publications
(559 reference statements)
0
1
0
Order By: Relevance
“…Among the patients with NSCLC, ALK gene alterations occur in approximately 3-7% of cases, consistent with findings from previous series [19,20]. Our study cohort demonstrated a similar prevalence of ALK alterations as reported in NSCLC patients [19,20].…”
Section: Discussionsupporting
confidence: 92%
“…Among the patients with NSCLC, ALK gene alterations occur in approximately 3-7% of cases, consistent with findings from previous series [19,20]. Our study cohort demonstrated a similar prevalence of ALK alterations as reported in NSCLC patients [19,20].…”
Section: Discussionsupporting
confidence: 92%
“…In a study by Fukuyoshi et al ( 26 ), 90 patients with breast cancer were assessed, although the EML4-ALK fusion was not detected. Another study ( 27 ) reported that in comprehensive genomic analyses, ALK fusions/rearrangements were identified in ~0.5–0.8% of cancers ( 28 , 29 ). Specifically, among patients with NSCLC, the prevalence of ALK fusions/rearrangements exceeds 3%, while the frequency of ALK fusions/rearrangements in non-NSCLC tumors is ~0.2%.…”
Section: Discussionmentioning
confidence: 99%
“…They are also repeatedly found in anaplastic large cell lymphomas, inflammatory myofibroblastic tumors, microsatellite-unstable colorectal carcinomas, KRAS mutation-negative pancreatic cancers, thyroid carcinomas, melanomas lacking common oncogene mutations, etc. While the NCI-MATCH trial failed to recruit a significant number of non-lung cancer patients with ALK rearrangements [80], there is a critical mass of case reports and small patient series strongly supporting the agnostic utilization of ALK inhibitors [81,82]. ROS1 is highly similar to ALK with regard to biochemical properties and the spectrum of tumor types carrying actionable rearrangements, although its alterations are detected at significantly lower frequencies [79].…”
Section: Other Mutated Oncogenes As Potential Agnostic Targetsmentioning
confidence: 99%